Formulation and evaluation of hyaluronic acid and adipic acid dihydrazide modified graphene quantum dot-based nanotherapeutics for paclitaxel-targeted delivery in breast cancer - Dilip O. Morani; Pravin O. Patil (Future Journal of Pharmaceutical Sciences)
Abstract Background Paclitaxel (PAC) was the first-ever natural chemotherapeutic agent for the treatment of breast cancer. However, it has some drawbacks like low water solubility, a long half-life, an unregulated rate of discharge, etc. Thus, this research paper aimed to develop PAC-loaded nanoparticles to lessen toxicity and boost PAC's solubility in water. In this case, hyaluronic acid (HA), graphene quantum dots (GQDs), and adipic acid dihydrazide (ADH) have been combined in a unique way to suggest pH-responsive nanoconjugates that can improve the therapeutic effect of medicinal molecule PAC with fluorescence and breast cancer targeting. Results The investigation of the particle dimensions revealed that the majority of the particles were discovered to be between 25–50 nm. Additionally, the loading efficiency of PAC in PAC@HA-ADH-GQDs nanoconjugates was 93.56% and the release of PAC was around 70% at pH 5 and 20% at pH 7.4 in 24 h. The MTT test's risk-free methodology successfully supports the classification of HA-ADH-GQD as a biocompatible substance as it demonstrates cell viability of more than 75%. Additionally, cellular uptake research has shown that MCF7 cancer cells absorbed more PAC@HA-ADH-GQDs than GQDs alone due to the presence of targeting agent HA. Conclusion In this study, we have investigated the potential of the hyaluronic acid motif (HA-ADH-GQDs)-attached nanotherapeutics (NTCs) as a carrier for simultaneous fluorescence imaging and pH-triggered targeted administration of anticancer medication for the treatment of breast cancer. The suggested study is innovative since anticancer drug delivery using HA-GQDs NTCs with adhesive capabilities of ADH has not been previously described. Graphical Abstract Diagrammatic representation of the preparation of PAC@HA-ADH-GQDs NTCs for breast cancer targeting